2002
DOI: 10.1080/1606635021000032366
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Exercise as an Addiction: A Review

Abstract: Theories regarding how exercise can become addictive, and studies of withdrawal from exercise are reviewed. Several physiological mechanisms, including endogenous opioids, catecholamines, and dopamine pathways, have been implicated in exerdse dependence. The higher levels of endogenous opioids found following strenuous exercise, has prompted researchers to suggest that a form of auto-addiction to these hormones might be responsible for continued excessive exercising in humans. As well, investigators have sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(65 citation statements)
references
References 32 publications
0
60
0
5
Order By: Relevance
“…career, social relationships) (123,124). Psychobiological mechanisms underlie the rewarding properties of both SUDs and exercise engagement (123,124,143), and studies examining the extent and nature of exercise addiction among those with SUDs who undergo exercise treatment regimens are needed.…”
Section: Outstanding Research Questionsmentioning
confidence: 99%
“…career, social relationships) (123,124). Psychobiological mechanisms underlie the rewarding properties of both SUDs and exercise engagement (123,124,143), and studies examining the extent and nature of exercise addiction among those with SUDs who undergo exercise treatment regimens are needed.…”
Section: Outstanding Research Questionsmentioning
confidence: 99%
“…Although current conceptualizations of exercise dependence suggest that the condition is an addiction (Adams & Kirkby, 2002), we use the term exercise dependence in place of exercise addiction to be consistent with terminology used in the Diagnostic and Statistical Manual of Mental Disorders. Based on criteria established for substance dependence, De Coverley Veale (1987), Hausenblas and Symons Downs (2002), and Adams, Miller, and Kraus (2003) have recommended that the criteria for diagnosing exercise dependence include three or more of the following symptoms within the same 12-month period: (a) tolerance: need of increasing exercise dosages for the same desired effect; ( b) withdrawal: psychophysiological disturbance when deprived of exercise; (c) intention ef fects: engage in more exercise than was intended; (d) loss of control: unable to minimize or control exercise behavior; (e) time: more time devoted to exercise-related activities; (f ) conf lict: exercise takes precedent over other life situations (i.e., social, occupational, recreational); and (g) continuance: continued exercise despite knowledge of having exercise-related physical or psychological problems.…”
Section: Exercise Dependencementioning
confidence: 99%
“…Almost three-quarters of the articles on excessive exercise conceptualized it as an addiction, with a biological orientation, highlighting the physiological mechanisms [136][137][138][139][140], or a biopsychosocial framework [141]. Other authors reviewed explanatory theories [142;143], or reported on empirical studies examining non-etiological aspects of excessive exercise [144][145][146][147][148].…”
Section: Excessive Exercisementioning
confidence: 99%